Synthesis, characterization, electrochemical and spectroelectrochemical properties of metal-free and metallophthalocyanines bearing electropolymerizable dimethylamine groups - KOCA, ATIF (ELSEVIER SCI LTD, 2013)
The synthesis and characterization of novel peripherally-tetra substituted metal-free 4 and metal-lophthalocyanines 5-7 are described for the first time in this study. All the new compounds are characterized by a combination of IR, H-1 and C-13 NMR, mass and UV-vis spectroscopy techniques. Electrochemical and spectroelectrochemical properties of metal-free, nickel(II), cobalt(II) and copper(II) phthalocyanines were investigated by using cyclic voltammetry and square wave voltammetry techniques. While all complexes give common reduction processes, they electropolymerized on the working electrode. Applied potentials and type of the metal center of the complexes affect the electropolymerization mechanism. Spectroelectrochemical and electrocolorimetric measurements exhibit that electrogenerated anionic species of the complexes have distinct color differences which are desire factors for electrochromic application of the complexes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Cobalt; Synthesis; Electropolymerization; Electrochemistry; Spectroelectrochemistry; SITU ELECTROCOLORIMETRIC CHARACTERIZATION; CROWN-ETHER MOIETIES; IN-SITU; MANGANESE PHTHALOCYANINE; SOLUBLE PHTHALOCYANINES; AGGREGATION PROPERTIES; MICROWAVE IRRADIATION; THIN-FILMS; COBALT; SUBSTITUENTS